Accounting Education: The Role of Universities in Imparting Sustainability Accounting Knowledge to the Stakeholders through Industry Linkages - Sylvester Onyango; Stephen Wanyoike Muchina; Stephen Irura Ng'ang'a (International Business and Accounting Research Journal, 2018)
In the wake sustainability agendas that lead to green growth in the developing countries, the focus has been in the practice and accounting for Social, Environmental and Economic (SEE) activities by both processing and manufacturing organizations. Organizations practice social responsibilities with the view of reaping long term returns or merely complying with regulations, information which is obtained from their annual reports via various media. These reports however, in the purview of knowledge are very scanty and whether the stakeholders understand and are aware of this sustainability accounting information remain very uncertain. However, organizations lack requisite capacity to unfold the elements of sustainability accounting and concurrently develop stakeholder knowledge. This gap remains unbridged since it is debatable how universities shall collate such knowledge and disseminate it to the users of accounting information (stakeholders). Therefore, there is need to develop sustainability accounting knowledge through university industry linkages that will further the realization of sustainability agenda. The paper is based on business sustainability model which looks at sustainability accounting issues. The study was informed by primary data collected from 93 factory unit managers and accountants sampled from 31 tea factories around Mount Kenya region, in testing the relationship between social reporting, environmental reporting, and sustainability accounting in regard to stakeholder theory. The study established significant relationship between the variables (social reporting, environmental reporting and sustainability accounting) and concludes that green growth need to be enhanced through sustainability accounting. In order to foster this, concrete knowledge has to be created by universities that conduct research by linking with industries and disseminate the knowledge to the stakeholders for awareness through stakeholder conferences and publications. The university curriculum need therefore, to incorporate the sustainability issues and passing to the learners too.